Copyright Challenges and Opportunities for the Integration of Generative Artificial Intelligence (GenAI) in Indonesian Higher Education Learning - Muh. Syah Quddus; Arika Dwi Astuti (Proceeding of the International Conference on Law and Human Rights, 2024)
The use of Generative Artificial Intelligence (GenAI) in higher education in Indonesia offers great opportunities, but faces significant challenges related to copyright. The technology is capable of generating new content that supports more adaptive learning, but raises questions regarding the ownership of intellectual works, especially in the context of “fair use” and copyright protection. This research aims to examine the legal challenges in the integration of GenAI in Indonesian higher education learning as well as opportunities for its development. The method used is juridical-normative research, by analyzing secondary data from relevant regulations, books, and journals. The results show that the lack of clarity in copyright regulations in Indonesia can hinder the optimal utilization of GenAI. Nevertheless, this technology offers significant potential to improve the personalization of learning and the quality of higher education in Indonesia, provided that comprehensive and specific regulations are developed soon.